Penerapan Akad Wakalah Bil Ujrah Pada Jasa Titip Online Freelance : Kajian Inovasi Ekonomi Syariah dalam Konteks Gig Economy - Haq, Muhammad Aufal; Mahira, Alfin Izza; Iskandar, Ahmad Muhaimin; Elfayanti, Yolanda Evrie (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2013)
Globalization encourages innovation in service providers such as freelance providers of goods delivery services (jastip). Jastip exists through social media and it can be seen that it is still in demand by consumers to get what they want. In order to develop the sharia economy, jastip can be implemented with the wakalah bil ujrah contract. The wakalah bil ujrah contract provides an overview of the economic side based on sharia, namely in the form of granting power to represent an action accompanied by wages for those who receive the power. In a further overview, all series of jastip activities are based on the digital economy pattern. The digital economy helps the development of jastip to become more massive. Meanwhile, jastip, if you want to rely on it as a form of sharia economic innovation with the wakalah bil ujrah contract. Through the wakalah bil ujrah contract, jastip can be more clearly regulated so as not to harm consumers who are users of the service.   Globalisasi mendorong adanya inovasi pada penyedia layanan jasa seperti freelance penyedia jasa titip (jastip) barang. Jastip ini eksis melalui media sosial dan dapat dilihat bahwa masih diminati konsumen untuk mendapatkan keinginannya. Dalam rangka pengembangan ekonomi syariah, jastip dapat dilaksanakan dengan akad wakalah bil ujrah. Akad wakalah bil ujrah memberikan gambaran pada sisi ekonomi berdasarkan syariah yaitu berupa pemberian kuasa untuk mewakilkan suatu tindakan dengan disertai upah bagi yang menerima kuasa. Dalam gambaran lebih lanjut, semua rangkaian kegiatan jastip disandarkan pada pola ekonomi digital. Ekonomi digital membantu perkembangan jastip menjadi lebih masif. Sedangkan jastip jika ingin disandarkan sebagai bentuk inovasi ekonomi syariah dengan akad wakalah bil ujrah. Melalui akad wakalah bil ujrah, jastip dapat menjadi lebih jelas regulasi yang dilaksanakannya agar tidak merugikan konsumen yang sebagai pengguna jasa layanan tersebut.